PENGABDIAN MASYARAKAT MELALUI PELATIHAN PENGEMBANGAN KEWIRAUSAHAAN TANAMAN HIAS UNTUK MENINGKATKAN KUALITAS PERMUKIMAN di Lingkungan Permukiman di Kelurahan Cipaganti, Kecamatan Coblong, Kota Bandung - Lucy Yosita; Kunthi Herma Dwidayati; R Diah Sri Hartati; Usep Surahman; Yan Nurcahya (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2022)
Cihampelas Bandung is one of the areas known as the center for souvenirs and shopping tourism in the city of Bandung. The pandemic covid-19 that occurred affected the economic condition due to the decreasing number of tourists arrival. In these conditions, innovations in activities that can support or empower human resources and the environment are needed. Urban farming is one form of potential that can be developed in this area, with open space that can be utilized. Although there are already a number of residents' yards, the conditions are still less productive. Based on this background, the service activity is to optimally empower the PKK community. One of them is by improving the ecological space, food security, and the resilience of the family economy in particular and the environment in general. The purpose of the activity is to provide additional understanding and knowledge to the community to protect the environment by planting useful ornamental plants; foster a sense of care and togetherness in caring for green open spaces; increase the economic potential of the community through new entrepreneurs by means of ornamental plant cultivation; and community empowerment, especially the PKK and Youth community groups. The activity is carried out in a participatory manner with the implementation in the form of ornamental plant training. The types of ornamental plants that were demonstrated in the training were caladium, aglonema, and sansiviera. The three plants were chosen because they are quite easy to breed and maintain.